The Effect of Problem-Based Learning Model on Learning Motivation and Problem-Solving Skills of Fourth Grade Elementary School Students - Prasetiawan, Fajar; Sofwan, Muhammad; Wulandari, Bunga Ayu (Journal of Innovation and Research in Primary Education, 2025)
This study aims to examine the effect of the Problem-Based Learning (PBL) model on (1) students’ learning motivation, (2) their problem-solving skills, and (3) the simultaneous influence of PBL on both variables in the context of Integrated Science and Social Studies (IPAS) for fourth-grade elementary students. A quantitative approach with a quasi-experimental design was employed, using a pretest-posttest non-equivalent control group design. The research was conducted at SDN 181/IX Berkah, involving 61 students divided into two classes: the experimental group received PBL instruction, while the control group used the STAD model. Data were collected through a learning motivation questionnaire and a problem-solving test developed based on Polya’s indicators. Instrument validity was confirmed through expert judgment, and reliability testing using Cronbach’s alpha yielded values of 0.82 for motivation and 0.79 for problem-solving. Data were analyzed using Kolmogorov–Smirnov for normality, Levene’s test for homogeneity, independent sample t-tests to test individual effects, and MANOVA to assess the simultaneous effect of the PBL model. The results revealed that the PBL model had a significant effect on learning motivation (p = .000), problem-solving ability (p = .000), and their simultaneous improvement (p = .000). These findings suggest that PBL is an effective instructional approach to enhance students’ cognitive and affective learning outcomes in IPAS learning